The Influence of Emotional Branding, Price Perception, Product Innovation and Trust in Customer Loyalty in F&B Industry - Muhammad Aria Wahyudi; Wawan Nurdiyansyah; Suryaniningsih Suryaniningsih (International Journal of Business, Law, and Education, 2026)
Analysis of this paper focuses on the impact of emotional branding, price perception, innovation in products, and trust on customer loyalty in the Food & Beverage (F&B) market. Due to rising competition and shifts in customer behavior, customer loyalty has become an important aspect of ensuring sustainability in the F&B market. By adopting a quantitative explanatory methodology, data has been gathered using an organized interview technique among customers with pre-buying experience of F&B products. By analyzing the gathered data using statistical methods, the impact of various independent factors is measured in terms of customer loyalty. Results of the analysis have shown that emotional branding, price perception, innovation in products, and trust have a joint positive impact on customer loyalty separately as well as together. On analyzing the data, trust is found to possess the highest predictive validity for customer loyalty, followed by emotional branding, innovation in products, and price perception. Also, customer loyalty in the F&B market has been influenced jointly by emotional attraction, innovation, price perception, and trust. Customer loyalty in the F&B market can have diverse interpretations among different customers, but customer loyalty in the F&B market has been found influenced jointly by emotional attraction, innovation, price perception.